2019
DOI: 10.3390/ma12244224
|View full text |Cite
|
Sign up to set email alerts
|

In-depth Investigation of Hg2Br2 Crystal Growth and Evolution

Abstract: Physical vapor transport (PVT) has frequently been adopted for the synthesis of mercurous bromide (Hg2Br2) single crystals for acousto-optic modulators. However, thus far, very few in-depth studies have been conducted that elucidate the growth process of the Hg2Br2 single crystal. This paper reports an in-depth investigation regarding the crystal growth and evolution behavior of the Hg2Br2 crystal with facet growth mode. Based on the experimental and simulation results, the temperature profile conditions conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…As discussed in our previous work, the large temperature difference of 30 °C between the upper zone (350 °C) and lower zone (320 °C) facilitates the single nucleus formation . However, Hg 2 Br 2 crystals grown at a low-temperature field (black line in Figure b 350 °C/320 °C) showing a rough surface during the growth (1# crystal in Figure c) are identified as a quasi-single crystal . Once the rough surface formed in the nucleation stage, it is hard to evolve to the smooth surface no matter how we adjust the growth parameters.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…As discussed in our previous work, the large temperature difference of 30 °C between the upper zone (350 °C) and lower zone (320 °C) facilitates the single nucleus formation . However, Hg 2 Br 2 crystals grown at a low-temperature field (black line in Figure b 350 °C/320 °C) showing a rough surface during the growth (1# crystal in Figure c) are identified as a quasi-single crystal . Once the rough surface formed in the nucleation stage, it is hard to evolve to the smooth surface no matter how we adjust the growth parameters.…”
Section: Resultsmentioning
confidence: 82%
“…Cho et al. deeply analyzed the effect of the ampoule position, the temperature gradient, and the temperature of the bottom heater on the nucleation and crystal growth by using the experiment and simulation . Our group also reported that the temperature field, growth rates, and vapor transport distances are key factors for obtaining high-quality crystals.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations